Adaptation to Coriolis force perturbations of postural sway requires an asymmetric two-leg model - Bakshi, Avijit; DiZio, Paul; Lackner, James R. (Journal of neurophysiology, 2019)
In the companion paper (Bakshi A, DiZio P, Lackner JR. J Neurophysiol. In press, 2019), we reported how voluntary forward-backward sway in a rotating room generated medial-lateral Coriolis forces that initially deviated intended body sway paths. Pure fore-aft sway was gradually restored over per-rotation trials, and a negative aftereffect occurred during postrotation sway. Force plate recordings showed that subjects learned to compensate for the Coriolis forces by executing a bimodal torque, the distribution of which was asymmetric across the two legs and of opposite sign for forward vs. backward sway. To explain these results, we have developed an asymmetric, nonparallel-leg, inverted pendulum model to characterize upright balance control in two dimensions. Fore-aft and medial-lateral sway amplitudes can be biomechanically coupled or independent. Biomechanical coupling occurs when Coriolis forces orthogonal to the direction of movement perturb sway about the ankles. The model includes a mechanism for alternating engagement/disengagement of each leg and for asymmetric drive to the ankles to achieve adaptation to Coriolis force-induced two-dimensional sway. The model predicts the adaptive control underlying the adaptation of voluntary postural sway to Coriolis forces. A stability analysis of the model generates parameter values that match those measured experimentally, and the parameterized model simulations reproduce the experimentally observed sway trajectories. NEW & NOTEWORTHY This paper presents a novel nonparallel leg model of postural control that correctly predicts the perturbations of voluntary sway that occur in a rotating environment and the adaptive changes that occur to restore faithful movement trajectories. This engaged leg model (ELM) predicts the asymmetries in force distribution and their patterns between the two legs to restore accurate movement trajectories. ELM has clinical relevance for pathologies that generate postural asymmetries and for altered gravitoinertial force conditions.